2021
DOI: 10.1088/1361-6382/ac3e76
|View full text |Cite
|
Sign up to set email alerts
|

Shadow and deflection angle of charged rotating black hole surrounded by perfect fluid dark matter

Abstract: We analysed the shadow cast by charged rotating black hole (BH) in presence of perfect fluid dark matter (PFDM). We studied the null geodesic equations and obtained the shadow of the charged rotating BH to see the effects of PFDM parameter $\gamma$, charge $Q$ and rotation parameter $a$, and it is noticed that the size as well as the shape of BH shadow is affected due to PFDM parameter, charge and rotation parameter. Thus, it is seen that the presence of dark matter around a BH affects its spacetime. We also i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 97 publications
1
29
1
Order By: Relevance
“…Many of the observed features and variations are markedly distinct, from Hydrogen plasma effects that have been previously explored in the literature [54][55][56][57][58][59], and electromagnetically neutral perfect fluid dark matter studies with phantom field-like equations of state considered earlier [43][44][45][46][47][48][49][50][51]. We find that the the photon sphere radius increases and the shadow radius decreases as the dark matter plasma effect becomes more pronounced, as a function of the millicharged particle mass and charge.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Many of the observed features and variations are markedly distinct, from Hydrogen plasma effects that have been previously explored in the literature [54][55][56][57][58][59], and electromagnetically neutral perfect fluid dark matter studies with phantom field-like equations of state considered earlier [43][44][45][46][47][48][49][50][51]. We find that the the photon sphere radius increases and the shadow radius decreases as the dark matter plasma effect becomes more pronounced, as a function of the millicharged particle mass and charge.…”
Section: Discussionmentioning
confidence: 54%
“…The effects on the black hole characteristics due to a modification of the spacetime background by any surrounding dark matter or exotic fields has also received much attention in recent years (see [37][38][39][40][41][42] and related references, for instance). In particular, there have been a few recent studies [43][44][45][46][47][48][49][50][51] that have considered effects due to a perfect fluid DM, with a special equation of state [52,53] that is quintessential or phantom field like with P r −ρ, surrounding a black hole. In contrast to these studies, our focus in this work will be on studying the effects due to a DM plasma, furnished by mCP components, taking phenomenologically viable mCP and semi-realistic astrophysical scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…For these regular black holes they have observed a decrease in the emission energy rate with the electric as well as the magnetic charge of the black holes. In a recent work the emission energy rate for a charged rotating black hole surrounded by perfect fluid dark matter has been investigated by Atamurotov et al [67]. They have shown that for the increasing values of the perfect fluid dark matter parameter and charge of the black hole, this emission rate decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent and related work for deflection angle caused by dark matter can be found in Refs. [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%